The Essentials of Finite Element Modeling and Adaptive Refinement : For Beginning Analysts to Advanced Researchers in Solid Mechanics. - Dow, John O. (Momentum Press, 2012)
Finite Element Analysis is a very popular, computer-based tool that uses a complex system of points called nodes to make a grid called a ""mesh. "" The mesh contains the material and structural properties that define how the structure will react to certain loading conditions, allowing virtual testing and analysis of stresses or changes applied to the material or component design. This groundbreaking text extends the usefulness of finite element analysis by helping both beginners and advanced users alike. It simplifies, improves, and extends both the finite element method while at the same t.